Evaluation of product development success: A student perspective - László Berényi; László Soltész (Administrative Sciences, 2022)
The time pressure on new product development under unpredictable conditions requires the renewal of the project management approach that suggests the prominent role of project managerial competencies in achieving project success. Project management education must be adjusted to understand students' opinions in the field. The study uses a survey among Hungarian engineering, business, and IT higher education students. The analysis aims to explore opinions about the main barriers to successful product development projects, and the expected ways of regulating the project by ANOVA and principal component analysis. The responses of 126 students confirm the appreciation of management competencies. Gaps in team composition, inadequate communication, common changes in the plans, and the lack of experience in similar development tasks are considered to be the main contributors to product development project failures. Collaboration and competition with external partners were found to be less essential factors. Students believe that regulation of the work is necessary, but the project team should be trusted to establish it. Beyond developing the curricula, the experience of this study can promote the successful execution of collaborative projects between companies and higher education institutions. It can establish expected student competencies to quickly become effective project team members.
Keywords: 350; new product development; project failure; project management competencies; student opinion; ANOVA; principal component analysis